Development of Malaysian grid system model for power flow and fault analysis study - Siti Sara Ramli (School of Electrical System Engineering, University Malaysia Perlis, 2011)
This project presents Development of 25 equivalent buses in South of Malaysia Grid System model for the load flow and fault analysis study. The iterative techniques are used to solve the load flow problem using computerized calculation. The iterative methods used in this project are Newton Raphson method, Fast Decouple method and Gauss Seidel method. In helping an efficient analysis, ETAP software has been used in solving the problem of power flow and fault analysis. To prove the analysis, Gauss Seidel method has 94 iterations. Newton Raphson method has very fast convergence speed. It needs only 3 iterations and zero mismatch on solving the load flow problem then followed by Fast Decouple method, 4 iterations. For fault analysis, ETAP short circuit analysis software can be used to analyze line-to-ground, line-to-line, and line-to-line-to-ground fault currents. The purpose of a short circuit study in this project is to evaluate the comparison between the fault at load center and the fault at generator terminal. From the analysis, the fault current at generator terminal is much higher than the load center.